Recurrent paralysis in benign thyroid disease - Cefrorella, Nora; López Susviela, Julio; Perdomo, Roberto (Cirugía del Uruguay, 1986)
Description of two clinical conditions in thyroid processes in which recurrential paralysis did not involve tumoral invasion. Not taking into account exceptions to the rule may lead to a mistake in diagnosis resulting in therapeutic error. Comments are made about the physiology and physio-pathological interpretation of symptoms: dysphonia, aphonia, respiratory alterations, etc. Stressed is the importance of phoniatric-reeducation.